Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18203/2349-3933.ijam20175135
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ankle brachial pressure index to arterial doppler USG in the diagnosis of peripheral vascular disease in diabetes mellitus

Abstract: Background: Peripheral artery disease(PAD) is a major macrovascular complication of diabetes mellitus. Patients with diabetes mellitus have an increased prevalence of PAD. However, due to associated neuropathy, common symptoms such as claudication are often masked and such patients often diagnosed late when limb threatening ischemia has already set in. Arterial colour doppler ultrasonography and ankle brachial pressure index are easy, non- invasive and often underutilised tools for diagnosis of PAD.Methods: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 5 publications
1
10
0
1
Order By: Relevance
“…Sensitivity of ABI was found to be 92.5%, Specificity - 88.33%, Positive Predictive Value (PPV) - 84.09% and Negative Predictive Value (NPV) - 94.64%, respectively. [ 15 ] The sensitivity of ABI measurement in comparison to DUS was found to be 88.89% and specificity 90.48% in the present study, similar to previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Sensitivity of ABI was found to be 92.5%, Specificity - 88.33%, Positive Predictive Value (PPV) - 84.09% and Negative Predictive Value (NPV) - 94.64%, respectively. [ 15 ] The sensitivity of ABI measurement in comparison to DUS was found to be 88.89% and specificity 90.48% in the present study, similar to previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Fourteen studies were retrospective [10][11][12][14][15][16][17]22,29,[33][34][35][36][37] and 19 were prospective. 13,[18][19][20][21][23][24][25][26][27][28][30][31][32][38][39][40][41][42]…”
Section: Resultsmentioning
confidence: 99%
“…For studies using CDUS, 15 of the 21 identified studies [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] reported the requisite data to perform the bivariate meta-analysis (sensitivity, specificity, number of participants with and without PAD) (Table S4). Mean sensitivity and specificity, DOR, ROC curve and AUC were calculated.…”
Section: What's New?mentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetic patients who have end-stage renal disease also show normal or falsely elevated ABI. Therefore, using their data nullifies the value of the test for diagnosis and follow-up [12].…”
Section: Discussionmentioning
confidence: 99%